2009
DOI: 10.1098/rspb.2009.1422
|View full text |Cite
|
Sign up to set email alerts
|

The Celtic fringe of Britain: insights from small mammal phylogeography

Abstract: Recent genetic studies have challenged the traditional view that the ancestors of British Celtic people spread from central Europe during the Iron Age and have suggested a much earlier origin for them as part of the human recolonization of Britain at the end of the last glaciation. Here we propose that small mammals provide an analogue to help resolve this controversy. Previous studies have shown that common shrews (Sorex araneus) with particular chromosomal characteristics and water voles (Arvicola terrestris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
110
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 43 publications
13
110
0
Order By: Relevance
“…These authors suggested that a cold tolerant lineage that initially colonized Britain and Ireland was replaced in Britain by an expanding lineage from Europe, which was assumed to have a fitness advantage under warmer environmental conditions. Piertney et al [58] and Searle et al [59] have used the same mtDNA replacement hypothesis to explain the Celtic fringe distribution seen in many British mammals, including the pygmy shrew (Sorex minutus), bank vole (Clethrionomys glareolus), field vole (Microtus agrestis) and water vole (Arvicola terrestris), which is strikingly similar to that described for the Celtic people [60]. In this study, however, the coexistence of both western and eastern lineages of N. leisleri in Ireland and Britain, and the fact that according to microsatellite analysis they constitute a single population, argues against mtDNA replacement to explain the absence of the western lineage in continental Europe.…”
Section: Discussion (A) Taxonomy and Phylogeographymentioning
confidence: 99%
“…These authors suggested that a cold tolerant lineage that initially colonized Britain and Ireland was replaced in Britain by an expanding lineage from Europe, which was assumed to have a fitness advantage under warmer environmental conditions. Piertney et al [58] and Searle et al [59] have used the same mtDNA replacement hypothesis to explain the Celtic fringe distribution seen in many British mammals, including the pygmy shrew (Sorex minutus), bank vole (Clethrionomys glareolus), field vole (Microtus agrestis) and water vole (Arvicola terrestris), which is strikingly similar to that described for the Celtic people [60]. In this study, however, the coexistence of both western and eastern lineages of N. leisleri in Ireland and Britain, and the fact that according to microsatellite analysis they constitute a single population, argues against mtDNA replacement to explain the absence of the western lineage in continental Europe.…”
Section: Discussion (A) Taxonomy and Phylogeographymentioning
confidence: 99%
“…The cytochrome b sequences were first used to separate the field vole material from a large set of Microtus samples collected across western Europe from southern Scandinavia to Iberia. These new field vole sequences were analysed together with 107 published sequences [14,16] from the Palaearctic range of the species. Sampling was heavily concentrated in the British Isles, which introduced a potential bias in the demographic analyses but nevertheless offered an important opportunity for their calibration (see below).…”
Section: Methodsmentioning
confidence: 99%
“…(b) Phylogenetic analyses Phylogenetic trees were inferred from the 204 distinct haplotypes and the phylogeographic structure was compared with that which was identified previously [14,16]. The trees were obtained using the neighbour-joining method implemented in MEGA v. 4.0.1 [19], the maximum-likelihood approach in PHYML v. 3.0 [20] and the Bayesian phylogenetic inference of MRBAYES v. 3.2 [21].…”
Section: Methodsmentioning
confidence: 99%
“…While this model has been central to our understanding of the population histories of the European biota, subsequent work suggests a more complex pattern of recolonization that can vary in relation to particular taxa, regions and time points [10]. One example is the proposal by Searle et al [11], who found that a general pattern for the recolonization of Britain can be inferred from studies of multiple small mammal species. Based on a range of genetic markers, they identified pairs of population groups in five different species, and in each case the two populations form either 'core' (roughly England, sometimes excluding the south coast) or 'peripheral' (Scotland, Wales and sometimes the south coast of England) populations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a range of genetic markers, they identified pairs of population groups in five different species, and in each case the two populations form either 'core' (roughly England, sometimes excluding the south coast) or 'peripheral' (Scotland, Wales and sometimes the south coast of England) populations. This pattern has been referred to as the 'Celtic fringe', since it bears a strong resemblance to the cultural and linguistic distinctions that today separate Scottish, Irish, Welsh, Manx and Cornish peoples from those in central and eastern England [11]. While it has been proposed to stem from multiple colonization events from different populations, the exact timing and nature of this process remains unclear.…”
Section: Introductionmentioning
confidence: 99%